Modelling the structures of occupational balance among community -dwelling retirees: a mixed-methods approach / Mohamad Qayum Mohamad Sabri - Mohamad Sabri, Mohamad Qayum (2024)
Retirement marks a crucial life transition wherein maintaining a sense of purpose and well-being becomes paramount. This transition calls for a renewed focus on occupational balance, which, despite its relevance for retirees' health and well-being, has had a noticeable scarcity of research among Malaysian retirees. To bridge this gap, we use in-depth interviews and a cross-sectional study to explore occupational balance comprehensively. While the literature on occupational balance does exist, it often presents inconsistent findings, thereby necessitating a localised examination to gain a deeper and context-specific understanding. This study aimed to (i) explore the experience of occupational balance post-retirement among retirees; (ii) determine the influence of proposed independent variables (time use and health status) on the occupational balance post-retirement among retirees; (iii) determine the influence of occupational balance post-retirement on the retirees’ life satisfaction; (iv) determine the mediating effects of occupational balance between time use or health status with life satisfaction; and (v) determine the moderating effects of demographic and socioeconomic status on the occupational balance structure post-retirement.